Job Stress of IT Employees in Tamilnadu – An Empirical Study - et. al., M. Mugil, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Stress is a part of our work. Beyond the threshold level, stress causes adverse effect on the physical and mental wellbeing of the workers, whatever may be the work done, proves the research studies. Information Technology (IT) industry employees’ jobs, though financially is attractive when compared with other industries, the experienced level of stress is significant greater. In the context of changing policies, globalization, liberalization, competition, downsizing, and arrival of brand-new innovation and technologies work becomes stressful naturally. The present study aims at addressing the problems of IT employees related to job stress. The present study attempted to throw light on the various problems of job stress among IT employees in Chennai city at Tamilnadu State. The tool “Job Stress Scale” was used to measure the stress in terms of ten categories of stressors: Role overload, Role ambiguity, Role conflict, Unreasonable group and political pressure, Responsibility for persons, Under participation, Powerlessness, Poor peer relations, Low status, and Strenuous working conditions. The 103 employees were drawn as a sample from five leading IT companies, occupying various positions. The data were obtained and analysed using correlational, Chi-Square, ‘t’ test, ANOVA and Factor Analysis. The results revealed that role conflict arose because of poor peer-relations. There was significant relationship between marital status of employees and job stress. There was association between role overload and responsibility for persons. Significant difference was found between married and unmarried employees with regard to job stress. No difference was found between different categories of employees. This study throws light on the problems related to job stress among IT employees that would be helpful in managing stress, evolving new policies and act as source for further research.